Tüketicilerin Kitap satın alma sürecinde rol oynayan unsurlar ve bu unsurların tüketicilerin demografik özellikleri açısından incelenmesi: İstanbul ilinde bir pilot çalışma - (:unkn) unknown (My University, 2009)
Özet: Pazarlamanın temelini oluşturan tüketicilerin satın alma davranışları, yazında büyük önem taşıyan konulardan biridir. Hangi mal veya hizmet olursa olsun satın alma kararı verilirken basit veya karmaşık bir satın alma karar süreci yaşanır. Pazarlamacılar içinse önemli olan, bu süreçte tüketicilerin kararlarını etkileyen faktörleri bilmek ve bunlara göre pazarlama çabalarını yönlendirebilmektir. Bu çalışmada tüketici satın alma karar sürecine konu olan ürün olarak kitap seçilmiştir. Kültürel pazarlamanın öneminin artışıyla, farklı bir boyut kazanan kitapların satın alınmasında etkili olan pek çok unsur bulunmaktadır. Çalışmayla bu unsurlar belirlenmeye çalışılıp, bu unsurların tüketicilerin demografik özelliklerine göre farklılık gösterip göstermediğine bakılarak kitap pazarlamacıları için yol gösterici olabileceği düşünülen öneriler sunulacaktır.

Abstract: Consumer purchase behavior forms a basis for marketing and is one of the critically important subjects in literature. No matter what the product or service purchased the consumer experiences a simple or complicated purchase decision process anyway. It is crucial for the marketers to know the factors that are effectual on the consumers' purchase decisions throughout this process and to direct the marketing activities in appropriate with these factors. In this study, book is determined to be the subject matter of the consumer purchase decision process. Have cultural products marketing gained ground; books have also become differently important. There are numerous factors that are effectual on the purchase decision of the books. This study aims to determine these factors and to explore whether these factors show significant differences according to the demographic characteristics of consumers. The study ends with beneficial information and managerial implications for book marketers.
Factors taking part in consumers' book purchase decision process and examination of these factors in terms of demographic characteristics of consumers: A pilot study in İstanbul